2012
DOI: 10.1016/j.sleep.2011.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Effect of three weeks of continuous positive airway pressure treatment on mood in patients with obstructive sleep apnoea: A randomized placebo-controlled study

Abstract: Background Patients with obstructive sleep apnoea (OSA) commonly have mood symptoms such as depression and anxiety. However, the results of randomized controlled trials on the therapeutic effect of CPAP on mood symptoms have been inconsistent. The present study examined whether 3 weeks of CPAP treatment had specific therapeutic effects on mood symptoms in patients with OSA compared with placebo. Methods A double-blind, parallel, randomized controlled trial using therapeutic and placebo CPAP was performed in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 23 publications
0
21
0
Order By: Relevance
“…76 However, in a double-blind, placebo control study, CPAP treatment dramatically decreased AHI but had no effect on depressed mood. 77 A limitation of these studies included small sample sizes and assessment of depression shortly after treatment duration possibly affecting the outcome.…”
Section: Discussionmentioning
confidence: 99%
“…76 However, in a double-blind, placebo control study, CPAP treatment dramatically decreased AHI but had no effect on depressed mood. 77 A limitation of these studies included small sample sizes and assessment of depression shortly after treatment duration possibly affecting the outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Multivariate analysis showed that chronic depressive symptoms were independently associated with the persistence of excessive daytime sleepiness, comorbid cardiovascular disease and female sex. This study overcame the methodological limitations of previous null studies [25,27,29] with a larger sample size, long-term CPAP use and inclusion of patients with baseline depression. However, the study was still observational with no placebo/sham CPAP arm.…”
Section: Cpapmentioning
confidence: 99%
“…In another study in |OSA comparing the effect of placebo CPAP, treatment CPAP and nocturnal supplemental oxygen, only supplemental oxygen showed significant improvement in psychological symptoms while a trend was observed towards improvement in depression score with CPAP treatment [26]. Another randomised trial from the same group compared the effects of therapeutic and placebo CPAP for 3 weeks on mood of patients with OSA [27]. Depression was assessed by POMS, Center for Epidemiological Studies Depression (CES-D) and BSI.…”
Section: Cpapmentioning
confidence: 99%
“…The literature linking SDB with some forms of psychopathology (e.g., ADHD) remains mixed [38,39] and the alleviation of SDB has not always produced improvements in mood symptoms [40]. Furthermore, much of the data linking SDB with different forms of psychopathology, and the effect of CPAP on neuropsychiatric improvement, come from small, shortterm studies [41].…”
Section: The Sdb-psychopathology Webmentioning
confidence: 99%